JAK3 pathway is constitutively active in B-lineage acute lymphoblastic leukemia. Issue 1 (January 2011) - Uckun, Fatih M; Pitt, Jason; Qazi, Sanjive
In this article, we report that primary leukemic B-cell precursors from B-lineage acute lymphoblastic leukemia (ALL) patients overexpress multiple JAK3-activating cytokines as well as their receptors. We also show that amplified expression of JAK3 pathway genes in B-lineage ALL is associated with steroid resistance and relapse. Our findings further demonstrate that several different diagnostic classes of B-lineage lymphoid malignancies exhibit upregulated expression of JAK3 pathway genes, which are associated with an overexpression of genes for JAK3-stimulatory cytokines with concomitant deficiency of JAK3-inhibitory signaling molecules. Thus, despite the rare occurrence of activating JAK3 mutations, JAK3 appears to be constitutively active and represents a viable molecular target in the treatment of a broad range of B-lineage lymphoid malignancies, including B-lineage ALL.